2003
DOI: 10.1016/s0002-9440(10)63834-5
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to Mesenchymal Transition in Human Breast Cancer Can Provide a Nonmalignant Stroma

Abstract: A breast carcinoma biopsy showed cytochemical evidence of epithelial mesenchymal transition and an ␣-smooth muscle actin-positive stromal reaction. To study the lineage, and the nature of the cells in the stromal reaction, we derived a novel cell line, HBFL-1, from the explanted biopsy. HBFL-1 cells are immortal and exhibit a shared non-random X-chromosome inactivation pattern with the epithelial tumor of origin. Yet they closely resemble normal, finite-life-span fibroblasts by morphology, lack of tumor format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
198
1
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(210 citation statements)
references
References 49 publications
(50 reference statements)
5
198
1
6
Order By: Relevance
“…Tumor fibroblasts play an important role in tumor development. Previous studies have been based on the hypothesis that tumor fibroblasts were recruited from the surrounding microvessels to the malignant tissues (Petersen et al, 2003;Puré, 2009). In serumcontaining medium, sphere clones exhibited fibroblast morphology after adherence, and the cells could be labeled by the fibroblast marker vimentin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor fibroblasts play an important role in tumor development. Previous studies have been based on the hypothesis that tumor fibroblasts were recruited from the surrounding microvessels to the malignant tissues (Petersen et al, 2003;Puré, 2009). In serumcontaining medium, sphere clones exhibited fibroblast morphology after adherence, and the cells could be labeled by the fibroblast marker vimentin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This process, referred to as ''epithelial to mesenchymal transition (EMT),'' intensifies the motility and invasiveness of many cell types and is often considered a prerequisite for tumor infiltration and metastasis. 3,4 Pancreatic cancer is the fourth leading cause of cancer-related deaths in the industrialized world. 21 Once pancreatic cancer is clinically evident, it rapidly develops metastatic lesions, frequently by the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This transition is considered to be an important event during malignant tumor progression and metastasis. [3][4][5] Periostin is a secretory protein that has been suggested to function as a cell adhesion molecule for preosteoblasts and to participate in osteoblast recruitment, attachment and spreading. 6,7 Recently, the expression of periostin has been implicated in the development of variety of carcinomas such as neuroblastoma, 8 epithelial ovarian cancer 9 and non-small cell lung carcinoma.…”
mentioning
confidence: 99%
“…Unfortunately, there is an increasingly accepted consensus suggesting that the inappropriate activation of the EMT processes contributes in part to the increased invasive and metastatic potential of various tumors [67][68][69][70][71][72][73][74]. There are also evidences exist associating the EMT process with the origin of CSCs and considering EMT as a precondition for cancer metastasis.…”
Section: The Notch Pathwaymentioning
confidence: 99%
“…There are also evidences exist associating the EMT process with the origin of CSCs and considering EMT as a precondition for cancer metastasis. Based on this, many researchers are striving to develop EMT as a target for cancer treatment [49,51,69,70]. resveratrol on human lung cancer, Wang H et al [75] found that resveratrol (trans-3,4,5 trihydroxy stilbene, found in several plants) was effective to increase the expression of epithelial phenotype marker E-cadherin and to downregulate the mesenchymal marker Fibronectin and Vimentin, which led them to conclude that the resveratrol could be used as an inhibitor of TGF-β1-induced EMT, in that it triggered the process of MET reversal in in virto conditions with A549 lung cancer cells whose invasiveness and metastasis were largely reduced [75].…”
Section: The Notch Pathwaymentioning
confidence: 99%